STUDY ON ECONOMIC AND ENVIRONMENTAL BENEFITS OF WASTE BANK INITIATIVES IN DKI JAKARTA PROVINCE - Renny Nurhasana (Universitas Andalas, 2014)
The aim of this study was to measure economic and environmental benefits, and also sustainability of Waste Bank in DKI Jakarta by conducting a field survey. The study found that Waste Bank activities have generated approximately IDR 11,628,433 (USD 1,199) of additional income to their members. The Waste Bank activities have also contributed to the reduction of waste volume by almost 4.55 tons or 15.2 m3 per month that equals to saving IDR 16,750,512/year (USD 1,727) of transportation cost and tipping fee. If the Waste Bank initiative can be scaled up to 5% of total households in Jakarta, the total economic benefits would be about IDR 17.27 billion (USD 1,78 million). As a social business, Waste Banks have also produced environmental benefits by increasing community awareness on 3Rs, thus, improving social cohesion and empowering society. In terms of sustainability, most Waste Banks are both financially and socially sustainable as business entities. While the economic benefits are relatively small, the environmental benefits are significant to the society.Keywords: Economic Benefit, Environmental Benefit, Jakarta Indonesia, Social Business, Waste Bank.